Paleoproductivity and paleoceanography of the last 4.3 Myrs at IODP Expedition 323 Site U1341 in the Bering Sea based on biogenic opal content. (March 2016) - Iwasaki, Shinya; Takahashi, Kozo; Kanematsu, Yoshiyuki; Asahi, Hirofumi; Onodera, Jonaotaro; Ravelo, A.C.
Abstract: Site U1341 in the southern Bering Sea was drilled and cored down to 600 meters below sea-floor (mbsf) during Integrated Ocean Drilling Program (IODP) Expedition 323, covering a nearly complete record of the last 4.3 million years (Myrs). Analyses of the biogenic opal content of sediments at the site provide detailed and useful information on past biological productivity and paleoceanographic changes that occurred in the region including shifts in the oceanographic condition during the intensification of the Northern Hemisphere Glaciation (NHG) and the Mid-Pleistocene Transition (MPT). An overall decreasing trend in the %biogenic opal record, combined with evidence from microfossil assemblages, indicates a gradual shift in environmental conditions during the last 4.3 Myrs, from warm and nutrient-rich conditions to cool conditions with sea-ice. On the other hand, biogenic opal mass accumulation rates (MAR) were high during 2.6–2.1 Ma after the intensification of the NHG, unlike in the western North Pacific. High biological productivity during this specific interval is consistent with the results of previous studies in the other Marginal Seas, possibly suggesting that iron leakage from the Bering Continental Shelf occurred. After the MPT, the data suggest that there was sea-ice expansion and discharge of lithogenic matter during glacial periods, and high productivity during interglacial periods.